The constitutional court as a foundation of legal defense in Kazakhstan - Kalmaganbetova, D.B.; Yessentemirova, A. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The year 2022 is becoming a landmark year for Kazakhstan, radically transforming the legal system and making fundamental changes. Political events that took place in the republic itself prompted President K. Tokayev to change the course of political reforms. In 2023, the Constitutional Court was revived in the country. The Constitutional Court is a necessity inspired by modern realities. The current Constitutional Court is a relatively "young" institution, maintaining continuity, and is based on the experience of other countries and previous constitutional institutions of the country. The article analyzes all constitutional institutions that have functioned or are operating in the country. The historical prerequisites for the creation of these institutions, their features, and specifics. The role of the Constitutional Court is defined and analyzed its activities. In addition, indicated the positive outcomes of the Constitutional Court’s activities. The activities of the Constitutional Court aimed, first, at eliminating gaps and ensuring effective protection of the Constitution. The new model of constitutional review assumes the supremacy of the Constitution. This paper analyzes judicial practice and its role in solving current problems of the socio-legal development of the country. Presented the aspects of the importance of deciding on the revival of the constitutional court.